2017
DOI: 10.1007/s00382-017-3634-9
|View full text |Cite
|
Sign up to set email alerts
|

How does dynamical downscaling affect model biases and future projections of explosive extratropical cyclones along North America’s Atlantic coast?

Abstract: Explosive extratropical cyclones (EETCs) are rapidly intensifying low pressure systems that generate severe weather along North America's Atlantic coast. Global climate models (GCMs) tend to simulate too few EETCs, which may partly be related to their coarse horizontal resolution and poorly resolved moist diabatic processes. This study explores whether EETC frequency biases can be reduced through dynamical downscaling, and whether this affects climate change projections of storms along North America's Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…On the other hand, explosive ETCs are projected to shift northwards in the NH Pacific, with no significant frequency changes when averaged across the Pacific basin. Dynamical downscaling experiments showed that the projected reduction of explosive ETC frequency in the Atlantic is not very sensitive to changes in the horizontal model resolution, possibly due to the lack of impact of resolution on the maximum Eady growth rate in that study [89]. This result is somewhat in contrast with other studies that show increased sensitivity to warming in higher resolution models [90].…”
Section: Etc Intensitycontrasting
confidence: 80%
“…On the other hand, explosive ETCs are projected to shift northwards in the NH Pacific, with no significant frequency changes when averaged across the Pacific basin. Dynamical downscaling experiments showed that the projected reduction of explosive ETC frequency in the Atlantic is not very sensitive to changes in the horizontal model resolution, possibly due to the lack of impact of resolution on the maximum Eady growth rate in that study [89]. This result is somewhat in contrast with other studies that show increased sensitivity to warming in higher resolution models [90].…”
Section: Etc Intensitycontrasting
confidence: 80%
“…However, here we also find an overall decrease in intense cyclones over the Pacific on top of the northeastward shift, and the region of decrease in the Atlantic is located far downstream of the region that Seiler and Zweirs found for the decrease in the frequency of explosive cyclones (over the western Atlantic just off the coast of North America). Seiler and Zwiers (2016) also showed that the mean vorticity (at 850 hPa) of explosive cyclones is projected to increase in the Atlantic-this is consistent with our finding that the 850-hPa extreme wind frequency may increase off the east coast of North America extending toward Europe, but similar increases in extreme winds are not found near the surface.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…The current results are more consistent with those for explosive cyclones. The projections of a northeastward shift in the Pacific and a significant decrease in extreme surface cyclones in the Atlantic are more or less consistent with the results of Seiler and Zwiers (2016). However, here we also find an overall decrease in intense cyclones over the Pacific on top of the northeastward shift, and the region of decrease in the Atlantic is located far downstream of the region that Seiler and Zweirs found for the decrease in the frequency of explosive cyclones (over the western Atlantic just off the coast of North America).…”
Section: Summary and Discussionsupporting
confidence: 80%
“…However, they also found a slight increase in maximum and average 10-m wind speeds off the coasts of the Northeastern United States. Seiler et al (2018) found a decrease in rapidly developing ETCs for two climate models along the East Coast of North America. In contrast, Marciano et al (2015) used the pseudo-global warming (PGW) approach to simulate 10 relatively strong (< 995 hPa) extratropical cyclones over U.S. East Coast for the current and future climates down to the 4-km grid spacing.…”
Section: Introductionmentioning
confidence: 92%